The Effect of CLAHE and Gamma Correction in Enhancement of Digital Radiographic Image for Weld Imperfection Detection - Abd Halim, Suhaila; HP Manurung, Yupiter; Mohamad, Shahidan; Firhan Morni, Mohamad (International Journal of Engineering and Technology, 2018)
Conventionally, the quality and acceptance of the welded joints are evaluated manually by human expert called radiography inspector. The results from the process are slow, inconsistent and even the same expert may give different results due to the poor quality of the captured image. In order to make the inspection becomes reliable, image processing could be adopted to improve and enhance the quality of the image. The purposes of this paper are to implement different image processing methods on removing image noise and enhancing image contrast, evaluate the performance image processing methods and detect weld imperfection from digital radiographic image. At the first stage, image processing is implemented on radiographic image that contains imperfection using Average Filter, Circular Averaging Filter and Gaussian Filter as noise removal while Contrast Limited Adaptive Histogram Equalization (CLAHE) and Gamma Correction (GC) as the image contrast enhancement. Then, the existence of the imperfection in processed image is extracted using Region Growing. The development of the algorithm is implemented using MATLAB 2009a. The results of the application of image processing methods show some improvement in term of accuracy as compared with manual inspection by radiography inspector. Hence, it could reduce the cost of inspection process in term of labor and time.Â